2020
DOI: 10.7554/elife.51984
|View full text |Cite
|
Sign up to set email alerts
|

Symptom evolution following the emergence of maize streak virus

Abstract: For pathogens infecting single host species evolutionary trade-offs have previously been demonstrated between pathogen-induced mortality rates and transmission rates. It remains unclear, however, how such trade-offs impact sub-lethal pathogen-inflicted damage, and whether these trade-offs even occur in broad host-range pathogens. Here, we examine changes over the past 110 years in symptoms induced in maize by the broad host-range pathogen, maize streak virus (MSV). Specifically, we use the quantified symptom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…When λ values are close to 0, the traits are likely to have evolved independently of phylogeny. Alternatively, λ values close to 1 indicate that traits display a strong phylogenetic signal and arise according to a classic Brownian diffusion model in a manner that is perfectly consistent with the phylogenetic relationships of the organisms from which the trait measurements were taken (Lemey et al 2010;Vrancken et al 2015;Monjane et al 2020). Finally, we also used continuous character mapping reconstructions to estimate pairwise correlations among traits extracted from the precision matrix (Vrancken et al 2015), i.e., correlation values that thus accounted for the phylogenetic relatedness of Cataglyphis species.…”
Section: Phylogenetic Inference and Patterns Of Trait Co-evolutionmentioning
confidence: 99%
“…When λ values are close to 0, the traits are likely to have evolved independently of phylogeny. Alternatively, λ values close to 1 indicate that traits display a strong phylogenetic signal and arise according to a classic Brownian diffusion model in a manner that is perfectly consistent with the phylogenetic relationships of the organisms from which the trait measurements were taken (Lemey et al 2010;Vrancken et al 2015;Monjane et al 2020). Finally, we also used continuous character mapping reconstructions to estimate pairwise correlations among traits extracted from the precision matrix (Vrancken et al 2015), i.e., correlation values that thus accounted for the phylogenetic relatedness of Cataglyphis species.…”
Section: Phylogenetic Inference and Patterns Of Trait Co-evolutionmentioning
confidence: 99%
“…Il a également été constaté que les virus des plantes étaient capables de manipuler à la fois leurs hôtes et/ou leurs vecteurs afin de maximiser leur transmission [52][53][54][55]. Enfin, des travaux récents ont mis en évidence l'existence d'un compromis évolutif entre la virulence d'un phytovirus (maize streak virus, agent causal de la striure du maïs) et sa fréquence de transmission [56].…”
Section: L'écologie Des Virus De Plantes Et La Révolution De La Biologie Moléculaireunclassified
“…Previous studies showed that, as with other geminiviruses, recombination played a decisive role in the evolution of MSV. Particularly, a recombination event that occurred in the mid-19 th century between ancestral MSV-B and MSV-G/-F strains probably led to the emergence, the efficient dispersion across Africa and the progressive adaptation of MSV-A strain to maize that became a major pathogen to this crop (Harkins et al 2009; Monjane et al 2020, 2011; Varsani et al 2008).…”
Section: Introductionmentioning
confidence: 99%